Defining Pediatric Malnutrition: A Paradigm Shift Toward Etiology‐Related Definitions. Issue 4 (25th March 2013) - Mehta, Nilesh M.; Corkins, Mark R.; Lyman, Beth; Malone, Ainsley; Goday, Praveen S.; Carney, Liesje (Nieman); Monczka, Jessica L.; Plogsted, Steven W.; Schwenk, W. Frederick; ,
Abstract : Lack of a uniform definition is responsible for underrecognition of the prevalence of malnutrition and its impact on outcomes in children. A pediatric malnutrition definitions workgroup reviewed existing pediatric age group English‐language literature from 1955 to 2011, for relevant references related to 5 domains of the definition of malnutrition that were a priori identified: anthropometric parameters, growth, chronicity of malnutrition, etiology and pathogenesis, and developmental/ functional outcomes. Based on available evidence and an iterative process to arrive at multidisciplinary consensus in the group, these domains were included in the overall construct of a new definition. Pediatric malnutrition (undernutrition) is defined as an imbalance between nutrient requirements and intake that results in cumulative deficits of energy, protein, or micronutrients that may negatively affect growth, development, and other relevant outcomes. A summary of the literature is presented and a new classification scheme is proposed that incorporates chronicity, etiology, mechanisms of nutrient imbalance, severity of malnutrition, and its impact on outcomes. Based on its etiology, malnutrition is either illness related (secondary to 1 or more diseases/injury) or non–illness related, (caused by environmental/behavioral factors), or both. Future research must focus on the relationship between inflammation and illness‐related malnutrition. We anticipate that the definition of malnutrition will continue to evolve with improved understanding of the processes that lead to and complicate the treatment of this condition. A uniform definition should permit future research to focus on the impact of pediatric malnutrition on functional outcomes and help solidify the scientific basis for evidence‐based nutrition practices.